Children : the vanished childhood : an empirical study - Ghosh, Swati, 1977-; Sinha, Debotosh (New Delhi : Concept Publishing Company Pvt. Ltd., 2017)
Study with reference to Kolkata, India.
Includes bibliographical references (pages 265-269) and index.
Keywords: Street children -- India -- Kolkata -- Social conditions